2017
DOI: 10.1210/en.2017-00208
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Corticosterone Treatment During Adolescence Has Significant Effects on Metabolism and Skeletal Development in Male C57BL6/N Mice

Abstract: Glucocorticoids are potent modulators of metabolic and behavioral function. Their role as mediators in the "stress response" is well known, but arguably their primary physiological function is in the regulation of cellular and organismal metabolism. Disruption of normal glucocorticoid function is linked to metabolic disease, such as Cushing syndrome. Glucocorticoids are also elevated in many forms of obesity, suggesting that there are bidirectional effects of these potent hormones on metabolism and metabolic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 70 publications
9
31
0
Order By: Relevance
“…Over the long term, at the end of the recovery period fasting glucose levels tended to remain lower, while glucose clearance was similar to that of the VEH mice. These results were in line with a recent study using the same animal model but in younger mice (3-week-old mice; Kinlein et al 2017). Nevertheless, differences with other previous studies, which reported hyperglycemia and glucose intolerance using the same animal model (Karatsoreos et al 2010, Fransson et al 2013, could be explained by considering the method of CORT dosage.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…Over the long term, at the end of the recovery period fasting glucose levels tended to remain lower, while glucose clearance was similar to that of the VEH mice. These results were in line with a recent study using the same animal model but in younger mice (3-week-old mice; Kinlein et al 2017). Nevertheless, differences with other previous studies, which reported hyperglycemia and glucose intolerance using the same animal model (Karatsoreos et al 2010, Fransson et al 2013, could be explained by considering the method of CORT dosage.…”
Section: Figuresupporting
confidence: 91%
“…In order to establish an accessible method to study CS remission, we used a reversible mouse model of hypercortisolism previously described by Karatsoreos et al (2010) that reproduces the CS phenotype, including increased adiposity, decreased lean mass and elevated plasma insulin levels. Although other authors have also previously characterized the active phenotype of this reversible model of CS in detail (Karatsoreos et al 2010, Morgan et al 2014, Yu et al 2014, only a few studies have been published regarding the long-term effects of previous GC treatment on metabolic target tissues, with inconsistent results depending on corticosterone (CORT) dose, age at treatment initiation and the time point of analysis during the recovery period (Cassano et al 2012, Auvinen et al 2013, Fransson et al 2013, Kinlein et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Corticosterone is a glucocorticoid in rodents, higher levels of which were reported in obese rats [ 38 ]. Since some reports showed that corticosterone is associated with metabolic diseases [ 39 , 40 ], we speculated that corticosterone would respond to HSD and time-restricted feeding. However, no significant alteration was observed ( Fig 5B ).…”
Section: Discussionmentioning
confidence: 99%
“…122 Interestingly, when glucocorticoids were administered in adolescent mice, blunted growth rate, induction of glucose clearance, and decreased bone density was observed. 123 These experimental models clearly demonstrated the ability of prolonged corticosterone to recapitulate symptoms typically found in adult Cushing syndrome in men.…”
Section: In Obesity and The Metabolic Syndromementioning
confidence: 84%